Environmental management as a strategy to control scorpion infestation in two areas of the state of São Paulo, Brazil (Research, Society and Development, 2026)
Scorpion stings represent a serious public health problem in the state of São Paulo, especially in urban areas, and it is necessary to control the size of their populations. In this sense, this study was carried out with the objective of evaluating the environmental management used as a control strategy. Areas in the municipalities of Hortolândia and Mogi Mirim, which had scorpion infestation and community health agents, were selected. With guidance and regular visits, carried out in three cycles of inspections of the properties every six months, information was gathered on the housing conditions (indoor and out-of-home), educational actions were carried out and guidance was given on improvements to the property, to prevent the presence of scorpions. On average, 1,330 homes were worked on/cycle. Many of the properties surveyed were residential (88.6%). For the intra-household, no change in the condition found was observed when comparing the first visit with the others. For the peridomicile, an improvement was observed in the conditions of vegetation pruning and in the annexes with plastered walls, but worsening for the accumulation of useless objects and debris. There was a decrease in the number of scorpions found during the inspections carried out. The condition of properties, with lack of maintenance and the presence of material in the peridomicile are risk factors that allow the presence of scorpions. Regular visits to properties can contribute to a reduction in scorpion sightings, which confirms management activity as one of the surveillance and control strategies, with repercussions on the occurrence of accidents.